Implementation Problem Based Learning Methods in The Subject of History Islamic Culture In Fostering Religious Character Student At MAN 2 Kota Malang - Shalihah, Nilna Nabilatus; Sari, Tri Retno Khalistha (Edumaspul: Jurnal Pendidikan, 2023)
The implementation of the problem-based learning method aims to improve student learning outcomes and foster the religious character of grade X-IPA1 students at MAN 2 Kota Malang where learning the history of islamic culture presents a lot of rote material that can cause boredom and decrease in quality, especially in student learning outcomes. To overcome these problems, active learning strategies are needed that can arouse students' enthusiasm in learning. One of them is to use the Problem based learning method. The results shown by this research are: (1) Planning of the implementation of the problem based learning method, namely compiling lesson plans, compiling teaching materials, preparing teaching materials and making measuring learning outcomes. (2) The implementation of the problem based learning method is carried out in 2 stages of che cycle with pre-action and post-action posttest in cycle I and cycle II which can foster students religious character, (3) Evaluation of implementation the problem based learning method, namely the improvement of learning outcomes and the form of religious character building in students. In the pre-action, the average student learning outcomes were 69,55 with 10 students complete and 24 students incomplete, in posttest I, the average student learning outcomes were 74,85 by being able to improve student learning outcomes, namely in the first cycle of student learning outcomes that achived learning completeness, namely 16 students completed and 18 students incomplete. And in posttest II, the average student learning outcomes were 87,94 with 30 students complete and 4 students incomplete.